2017
DOI: 10.5327/z2594539420170000197
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ultrasonographic features and histopathological findings of breast lesions in biopsies

Abstract: Imaging exams are fundamental tools to characterize palpable lesions and to early detect those not identified on the physical examination. However, the correct interpretation of these findings should be done by correlating them with the probable histological diagnosis of the lesion, and performing the appropriate treatment in a timely manner. The Breast Imaging-Reporting and Data System (BIRADS ® ) is the system used for this association, which characterizes the findings in mammography, ultrasonography and mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…This The pathological results of the tru-cut biopsy revealed 27 cases non-malignant (8 cases benign neoplasms , 20 cases inflammatory breast disease ) , 13 cases malignant breast carcinoma as following 6 of the cases were fibro adenoma , 2 cases were intra ductal papilloma ,10 cases benign proliferative fibroadenomatosis ,2 cases chronic inflammatory breast mastopathy ,2 cases granulomatous mastitis ,4 cases fat necrosis ,one case fibrocystic disease ,6 cases invasive ductal carcinoma ,4 cases invasive lobular carcinoma, 3 cases invasive breast carcinoma tubule-lobular Table (2) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This The pathological results of the tru-cut biopsy revealed 27 cases non-malignant (8 cases benign neoplasms , 20 cases inflammatory breast disease ) , 13 cases malignant breast carcinoma as following 6 of the cases were fibro adenoma , 2 cases were intra ductal papilloma ,10 cases benign proliferative fibroadenomatosis ,2 cases chronic inflammatory breast mastopathy ,2 cases granulomatous mastitis ,4 cases fat necrosis ,one case fibrocystic disease ,6 cases invasive ductal carcinoma ,4 cases invasive lobular carcinoma, 3 cases invasive breast carcinoma tubule-lobular Table (2) .…”
Section: Resultsmentioning
confidence: 99%
“…With the goal the identification from claiming breast nodules to diagnosing malignancy forerunner lesions in the recent past clinical manifestations may be essential, acknowledging its right on time finding permits a lesquerella Forceful medication and yet additional viable to these illnesses [2].…”
Section: Introductionmentioning
confidence: 99%
“…Combining both modalities boast greater sensitivity and specificity for detecting breast lesions. Silva and Furtado ( 16 ) in a study of 110 cases reported that ultrasound features of breast lesions have a high predictive value, significantly influencing the recommended management and outcome. This study showed that all patients with radiological imaging with high suspicion of malignancy had a histopathological diagnosis of breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies have greatly aided in the detection of non-palpable breast lesions, with emphasis on mammography, which identifies micro-calcifications, asymmetries and nodules, and on mammary ultrasonography (US), which is the most commonly used complementary method to characterize mammographic findings or to assist in the investigation of dense breasts. The identification of lesions suspicious of malignancy determines the need of cytological or histopathological evaluation through a minimally invasive procedure, whose arsenal consists basically of fine needle aspiration (FNAB) or core-biopsy (Silva et al, 2017). However, early detection requires an accurate and reliable diagnosis which should also be able to distinguish benign and malignant tumors.…”
Section: Introductionmentioning
confidence: 99%